2007
DOI: 10.1103/physrevlett.98.026601
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Carrier and Impurity Concentrations in AnnealedGa1xMnxAs: Intrinsic Anomalous Hall Effect

Abstract: Investigating the scaling behavior of annealed Ga 1ÿx Mn x As anomalous Hall coefficients, we note a universal crossover regime where the scaling behavior changes from quadratic to linear. Furthermore, measured anomalous Hall conductivities in the quadratic regime when properly scaled by carrier concentration remain constant, spanning nearly a decade in conductivity as well as over 100 K in T C and comparing favorably to theoretically predicated values for the intrinsic origins of the anomalous Hall effect. Bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…For B Ͼ 0.5 T, the AHE saturates because of the saturation of magnetization. 35,36 To ascertain the origins of AHE, we examine the scaling relationship xy ϰ xx n at 20 K for a series of Ge 1−x Mn x Te. The field dependencies of the R H curves are in good agreement with the M-H curves obtained by SQUID for both samples.…”
Section: Resultsmentioning
confidence: 99%
“…For B Ͼ 0.5 T, the AHE saturates because of the saturation of magnetization. 35,36 To ascertain the origins of AHE, we examine the scaling relationship xy ϰ xx n at 20 K for a series of Ge 1−x Mn x Te. The field dependencies of the R H curves are in good agreement with the M-H curves obtained by SQUID for both samples.…”
Section: Resultsmentioning
confidence: 99%
“…The anomalous Hall coefficient R A is proportional to R xx n , where n depends on the mechanism giving rise to the anomalous Hall resistance [24,25]. Experimentally, it is typically found that n2 in highly doped, lightly compensated (Ga,Mn)As films [5,8,26], while n1 has been reported for highly compensated samples [8,26].…”
mentioning
confidence: 99%
“…4 In this context magnetotransport measurements on Ga 1−x Mn x As-and especially the anomalous Hall effect ͑AHE͒-have played a major role in clarifying these issues. [5][6][7][8] While most efforts for identifying the mechanisms of conduction-impurity band with weak localization 9,10 versus true disordered metal with delocalized holes 11,12 -have so far been focused on Ga 1−x Mn x As with high Mn concentrations, 13 relatively little attention has been given to the case of insulating samples, where impurity band conduction is certain to occur. 14 In this work we have carried out AHE measurements on Ga 1−x Mn x As epilayers with low Mn concentration ͑x = 0.014͒ in high magnetic fields ͑up to 18.0 T͒, where aligning all Mn spins along the field direction makes it possible to extract the ordinary Hall coefficient from the Hall data.…”
mentioning
confidence: 99%